ChemInform Abstract: Nucleophilic β‐Carbon Activation of Propionic Acid as a 3‐Carbon Synthon by Carbene Organocatalysis. Issue 48 (December 2015) - Jin, Zhichao; Jiang, Ke; Fu, Zhenqian; Torres, Jaume; Zheng, Pengcheng; Yang, Song; Song, Bao‐An; Chi, Yonggui Robin
Abstract: An enantioselective reaction of α‐ketoesters (I) with propionic acid proceeds readily in the presence of an optically active indanol‐derived triazolium catalyst to afford chiral lactones (III).